Umetna inteligenca v luči praktične pastoralne teologije - Šegula, Andrej (Bogoslovni vestnik, 2024)
The article discusses the role of the Church's Magisterium in the context of the 2021–2024 Synod and its connection with artificial intelligence (AI), particularly its place in practical pastoral theology. When the Church's Magisterium addresses AI, it primarily promotes dialogue on the ethics and morality of AI development. The article demonstrates how the Pope's guidelines concretely influence pastoral theology. The Pope emphasizes respect for human dignity, transparency, impartiality, reliability, as well as safety and privacy in the use of AI. Recently, Pope Francis has particularly highlighted the need for ethical regulation of AI to ensure it remains in service to humanity. Given that we are in the midst of the Synod (2021–2024), the article examines the role of AI in the context of the Synod itself. In conclusion, some specific pastoral guidelines are proposed.
Keywords: AI ethics; artificial intelligence; cerkveno učiteljstvo; Church's Magisterium; etičnost UI; pastoral care; pastorala; sinoda; synod; umetna inteligenca